Study on needle anatomical structure and drought resistance of 15 spruce species - ZHAO Li; BAO Xiulan; WANG Fude; FU Sheng; LIU Lijie; HUO Kaiyu (Xibei zhiwu xuebao)
[Objective] The study aims to explore the relationship between the anatomical structure of different spruce needles and their drought resistance, to provide reference for spruce conservation research and screening of excellent germplasm resources. [Methods] 15 spruce species that were introduced and cultivated for more than 25 years in Hohhot arboretum were used as materials. The anatomical structure of needles was observed by the freehand section technique and the related indexes were analyzed. [Results] (1) The needles of 15 spruce species were composed of cuticle, epidermis, hypodermis, mesophyll tissue, endodermis, stele tissue, and so on. The mesophyll had no differentiation of palisade tissue and spongy tissue. (2) There were significant differences in different indexes of the anatomical structure of the needles among the 15 spruce species. Among them, the variation coefficient of the stele area was the largest (22.83%), and the variation coefficient of the cuticle thickness was the smallest (9.69%). (3) The contribution of each index of the spruce needle structure to stress drought resistance was: Subcortical thickness > stele area> stele thickness > needle cross-sectional area > cuticle thickness > endodermis cell length > epidermis thickness > pore number in needle cross-section > endodermis thickness. (4) The 15 spruce species were divided into four categories by cluster analysis, which reflected the differences in developmental degree of the protective tissue, nutritional tissue, and transfusion tissue of the tested plants. [Conclusion] The needle anatomical structure of the 15 spruce species can adapt to the environment in various forms. By constructing the developed cuticle, epidermal cells, mesophyll cells, and stele tissues, the water storage and water use efficiency can be improved, so that they can survive in arid environment.